2019
DOI: 10.1080/21679169.2018.1551420
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic balance and gait speed improve in persons with Parkinson´s disease after Lee Silverman Voice Treatment (LSVT)-BIG training: a single subject experimental design study

Abstract: BACKGROUND: Parkinson ś disease (PD) is characterized by small, slow movements affecting balance and gait. Lee-Silverman-Voice-Treatment-(LSVT)-BIG is an intensive intervention aiming to restore normal amplitudes of movements. This study aimed to examine whether LSVT-BIG influences dynamic balance and gait in persons with PD. METHODS: We used a Single-Subject-Experimental-Design with three phases; phase A (2 weeks) with no treatment, phase B (4 weeks) with LSVT-BIG-treatment and LSVT-BIG-hometraining, and phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…Eight participants had improvements in gait speed at one or more assessment time point, and four of those met MCID and two met MDC at EOT+4 (see Figure 2 and Table 3). These same six participants also met MCID in the UPDRS III Motor score which suggests that external cueing and task-based strategies may potentially decrease the impact of disability in PwPD through reduction in falls and impact on gait speed which is consistent with other similar studies [26,29,51].…”
Section: Outcome Measuressupporting
confidence: 88%
See 1 more Smart Citation
“…Eight participants had improvements in gait speed at one or more assessment time point, and four of those met MCID and two met MDC at EOT+4 (see Figure 2 and Table 3). These same six participants also met MCID in the UPDRS III Motor score which suggests that external cueing and task-based strategies may potentially decrease the impact of disability in PwPD through reduction in falls and impact on gait speed which is consistent with other similar studies [26,29,51].…”
Section: Outcome Measuressupporting
confidence: 88%
“…The positive impact of external cueing and task-based strategies on dynamic balance assessed by the MiniBEST has been supported by two studies [51,52], both with very small samples sizes (n = 2 and n = 1, respectively). Previous work identified two subcomponents of the MiniBEST, (1) "anticipatory control" and (2) "sensory orientation," as not sensitive to improvements.…”
Section: Outcome Measuresmentioning
confidence: 83%
“…Previous studies, mostly case studies (Fishel et al., 2020 ; Hirakawa et al., 2022 ; Iwai et al., 2021 ; Janssens et al., 2014 ; Kleppang & Jørgensen, 2020 ; Millage et al., 2017 ; Pascal et al., 2018 ), have shown that LSVT BIG training improves functional balance (Choi & Kim, 2022 ; Fishel et al., 2020 ; Hirakawa et al., 2022 ; Janssens et al., 2014 ; Kleppang & Jørgensen, 2020 ; Millage et al., 2017 ; Pascal et al., 2018 ) and PS (Iwai et al., 2021 ). The results of our study, which was a rater‐blinded randomized controlled trial, confirm the existing literature that LSVT BIG training improved balance.…”
Section: Discussionmentioning
confidence: 99%
“…They also found that all three exercise programs were effective in improving motor symptoms. Additionally, a lot of case studies found that LSVT BIG training improved functional mobility (Fishel et al, 2020;Flood et al, 2020;Hirakawa et al, 2022;Janssens et al, 2014), gait speed (Flood et al, 2020;Kleppang & Jørgensen, 2020;Millage et al, 2017), stride length (Flood et al, 2020), and motor symptoms (Fırat et al, 2023;Hirakawa et al, 2022;Iwai et al, 2021;Janssens et al, 2014;McDonnell et al, 2018;Millage et al, 2017;Ueno et al, 2017 (Fox et al, 2012). A review found results supporting that the online modified version of LSVT LOUD is not inferior to the standard protocol (Herd et al, 2012).…”
Section: Pretestmentioning
confidence: 99%
“…3 In addition, balance has been defined as the ability to maintain a (static) base of support and perform a task while maintaining a (dynamic) stable position. 13…”
Section: Introductionmentioning
confidence: 99%